Georgia : Request for Extended Arrangement Under the Extended Fund Facility and Cancellation of Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Georgia's Request for Extended Arrangement under the Extended Fund Facility and Cancellation of Stand-by Arrangement (SBA). The authorities in Georgia have formulated a comprehensive program to preserve macro and financial stability and advance structural reforms to bolster growth. The program envisions fiscal consolidation over the medium term, anchored in keeping debt at its current level while shifting spending toward capital investment to address infrastructure bottlenecks. The IMF staff supports the authorities' request for the approval of the three-year Extended Arrangement under the Extended Fund Facility and the cancellation of the SBA arrangement.